Research methods and report writing - Haslinda Abdullah (UPNM Press, 2019)
This book consists of 14 chapters which describes both quantitative and qualitative research methods and processes. It begins with providing an understanding on the research context and the ethical practices that should be observed in conducting research. It is followed with introducing stages in the research process and writing of chapters for a research proposal.The heart of a research, that is writing a problem statement, research questions, objectives and hypotheses, that leads to the process of developing a research framework are elaborated systematically and thoroughly. The literature review is a very critical process in research, hence, a step-by-step process of conducting a literature review as well as its purposes and importance are not overlooked. Both quantitative and qualitative research designs, data collections methods and data analysis are explained in independent chapters. The population and sampling as well as the final report writing for both research methods are also presented.